SAT0018 Pulmonary involvement in ankylosing spondylitis. (1st June 2001) - Sampaio-Barros, PD; Maeda, L; Rezende, SM; Zanardi, VA; Cerqueira, EF; Marques-Neto, JF; Menezes-Neto, JR; Samara, AM
Abstract : Background: Objectives: To analyse the subclinical pulmonary involvement in a series of patients with ankylosing spondylitis (AS). Methods: Prospective study analysing 52 patients with the diagnosis of AS according to the modified New York criteria. The patients were asymptomatic about lung complaints and were submitted to a pulmonary investigation that included plain chest radiography, pulmonary function test (PFT) and thoracic high-resolution computed tomography (HRCT). The results were compared with sex, race, dorsal spine involvement, thoracic diameter, smoking status and HLA-B27. There was predominance of male (81%), Caucasoid (75%), non-smoking (64%) and positive HLA-B27 (75%) patients, with dorsal spine involvement in 58%. Mean age was 40 years and mean disease duration was 16 years. Results: There were five patients (10%) with an altered plain chest radiography. PFT presented a restrictive pattern in 52% of the patients. Thoracic HRCT showed abnormalities in 21 patients (40%), predominantly nonspecific linear parenchymal opacities (19%), lymphadenopathy (12%), emphysema (10%), bronquiectasis (8%) and pleural involvement (8%). Male sex was statistically associated with dorsal involvement (p = 0.012). Non-Caucasoid race was associated with bronquiectasis (p = 0.044) and pleural involvement (p = 0.044) at the thoracic HRCT. Smoking patients presented more linear parenchymal opacities (p = 0.026) at the thoracic HRCT. Negative HLA-B27 was associated with an altered plain chest radiography (p = 0.011). Dorsal spine involvement was associated with restrictive pattern at PFT (p = 0.001) and linear parenchymal opacities (p = 0.032) at the thoracic HRCT. A lower thoracic diameter was observed in patients with dorsal spine involvement (p = 0.0001), restrictive pattern at PFT (p = 0.023) and linear parenchymal opacities (p = 0.015) at the thoracic HRCT. Conclusion: Subclinical pulmonary involvement is frequent in AS. The restrictive pattern at PFT is associated with dorsal spine involvement and a low thoracic diameter, whilst the thoracic HRCT presents a series of nonspecific alterations, predominating the linear parenchymal opacities.